2016
DOI: 10.3390/ijms17101712
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA in Control of Gene Expression: An Overview of Nuclear Functions

Abstract: The finding that small non-coding RNAs (ncRNAs) are able to control gene expression in a sequence specific manner has had a massive impact on biology. Recent improvements in high throughput sequencing and computational prediction methods have allowed the discovery and classification of several types of ncRNAs. Based on their precursor structures, biogenesis pathways and modes of action, ncRNAs are classified as small interfering RNAs (siRNAs), microRNAs (miRNAs), PIWI-interacting RNAs (piRNAs), endogenous smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
675
0
17

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 982 publications
(766 citation statements)
references
References 117 publications
4
675
0
17
Order By: Relevance
“…MicroRNAs are evolutionarily conserved, small (~22 nucleotide long) non-coding RNAs, involved in transcriptional and posttranscriptional regulation of biological processes (69). Recently, it has been shown that EVs are rich sources of miRNAs, since, being packed in membrane-coated vesicles, they are more protected from RNAses than in a naked form (70, 71).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs are evolutionarily conserved, small (~22 nucleotide long) non-coding RNAs, involved in transcriptional and posttranscriptional regulation of biological processes (69). Recently, it has been shown that EVs are rich sources of miRNAs, since, being packed in membrane-coated vesicles, they are more protected from RNAses than in a naked form (70, 71).…”
Section: Discussionmentioning
confidence: 99%
“…They act by inhibiting gene expression or by promoting gene degradation [131]. It is estimated that miRNAs regulate between 30 and 90% of genes in the genome, as a single miRNA may regulate hundreds of genes [132, 133].…”
Section: Mechanisms Of Innate Immune Activation In Ssmentioning
confidence: 99%
“…[21][22][23][24] They are single stranded and approximately 17-24 bases long. Aberrant miR activity has been associated with a number of neurodegenerative diseases including PD.…”
Section: Introductionmentioning
confidence: 99%